2018
DOI: 10.1515/shll-2018-0003
|View full text |Cite
|
Sign up to set email alerts
|

Context of learning and second language development of Spanish vowels

Abstract: Abstract The present study explored development in Spanish vowel production during a short-term study abroad program. The production patterns of a group of learners studying abroad in a 4-week program in the Dominican Republic were compared in terms of overall vowel quality, tendency to diphthongize /e/ and /o/, and vowel duration to those of a similar group of learners studying in the at-home context. Results revealed no significant changes or differences between groups in vo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 29 publications
0
4
1
1
Order By: Relevance
“…In contrast, Long et al. (2018) did not find any significant differences in the degree of vowel diphthongization that study abroad and at‐home learners produced after a 5‐week course in linguistics.…”
Section: Introductionmentioning
confidence: 81%
See 1 more Smart Citation
“…In contrast, Long et al. (2018) did not find any significant differences in the degree of vowel diphthongization that study abroad and at‐home learners produced after a 5‐week course in linguistics.…”
Section: Introductionmentioning
confidence: 81%
“…Although rhotics and stop consonants have received the most attention in the Spanish pronunciation literature, researchers have also examined other target structures, including velarization of /l/ (producing a dark /l/, [ɫ], in coda positions, such as realizing “caldo [broth],” as [ˈkaɫ.do] instead of [ˈkal.do]; Solon, 2017), vowel centralization (producing scwha‐like vowels; Menke & Face, 2010), and diphthongization of /e/ and /o/ (producing diphthongal vowels, [eɪ] and [oʊ], instead of the monophthongs [e] and [o]; Long et al., 2018). Results for /l/ and vowel centralization mirror findings for the rhotics and stop consonants—namely, a tendency to transfer English pronunciation features into Spanish accompanied by an incremental improvement toward more Spanish‐like pronunciation with increasing proficiency.…”
Section: Introductionmentioning
confidence: 99%
“…In spite of these few instances of variability, in contrast to English, Spanish is characterized by its lack of unstressed vowel reduction: stressed and unstressed vowels have the same quality but may differ in duration. This is an important feature to highlight when teaching pronunciation and should be emphasized right from the beginning of the learning process, as per the many studies that have demonstrated improvement when this feature is taught (Lord, 2005;Lord and Fionda, 2013;Long et al, 2018;Martínez Celdrán and Elvira-García, 2019).…”
Section: Targeting Features and Segments Shared By The Majority Of The Varieties Of The Target Languagementioning
confidence: 99%
“…........................................................................................ ตารางที ่ 8 ตารางสรุ ปผลการศึ กษาค่ าทางกลสั ทศาสตร์ .................................................................. ตารางที ่ 9 ตารางสรุ ปผลการศึ กษาร้ อยละการแบ่ งพยางค์ ได้ ตรงตามกฎ หรื อตรงกั บการคาดการณ์ ตารางที ่ 10 ตารางแสดงสมมติ ฐานของการวิ จั ย: ตั วแปรประสบการณ์ ไปแลกเปลี ่ ยน และระยะเวลา การเรี ยนภาษาสเปน . (Macleod, 2012;Cobb & Simonet, 2015) ระยะเวลาที ่ เรี ยนภาษาต่ างประเทศ (Menke & Face, 2008อ้ างถึ งใน Macleod, 2012Reeder, 1998อ้ างถึ งใน Macleod, 2012Zárate-Sández, 2011) และการเป็ นนั กเรี ยนและเปลี ่ ยนในประเทศที ่ ใช้ ภาษาต่ างประเทศเป็ นภาษาแม่ 1 เดื อนขึ ้ นไป (Stevens, 2011;Long et al, 2018) ในประเทศไทย มี นั กเรี ยนไปแลกเปลี ่ ยนยั งประเทศที ่ พู ดภาษาสเปนดั งที ่ กล่ าวไปข้ างต้ น โดยปกติ ผู ้ เรี ยน ภาษาที ่ สองที ่ ใช้ ชี วิ ตอยู ่ ในประเทศที ่ ใช้ ภาษานั ้ น ๆ มี โอกาสเรี ยนรู ้ ภาษาที ่ สองอย่ างมาก เนื ่ องจากจ าเป็ นต้ องใช้ ภาษา ที ่ สองในสถานการณ์ ต่ าง ๆ จึ งเป็ นประโยชน์ ต่ อการพั ฒนาความสามารถทางภาษาที ่ สอง (Coleman, 1998…”
Section: สารบั ญตารางunclassified
“…Keywords: pronunciation, Spanish, diphthong, hiatus, study abroad (1) (Face & Alvord, 2004;Chitoran & Hualde, 2003;Hualde & Prieto, 2002 (Aguilar, 1999;Isasa & Hualde, 2019) ทั ้ งนี ้ Aguilar (1999 (Quilis, 1988: 178 (Gubian et al, 2015;Torreira, 2007) (Kouti, 2015;Macleod, 2012) (Reeder, 1998อ้ างถึ งใน Macleod, 2012 (Reeder, 1998อ้ างถึ งใน Macleod, 2012 (Long et al, 2018 (Eichenbaum, 1997…”
Section: Introductionmentioning
confidence: 99%